A new biaxial tensile shear test method to measure shear behaviour of coated fabrics for architectural use. (1st November 2018) - Chen, Wujun; Gao, Chengjun; Zhang, Daxu; Wang, Ligang; Qiu, Zhenyu
Abstract: Shear properties of coated fabrics is poorly understood and the effects of shear stiffness on the behaviour of tensile fabric structures are usually ignored in the current design practice. The paper presents a new test method for the investigation of architectural coated fabric shear properties. The method relies on the biaxial pretension of cruciform specimens, where warp and weft yarns are oriented 45° with respect to the loading directions. Loading protocol is used to generate consecutive shear stress wave with specific biaxial tensile stress aligned with the yarns. An advanced biaxial tensile test system has been developed to implement biaxial loading by either displacement or force control strategy. Biaxial tensile shear tests of PVDF-coated polyester materials have been carried out to validate the new method. The implications of shear deformation, and material's viscosity and plasticity from the experimental results are addressed. The determination of shear stiffness is described and a comparison of results derived from different methods has been made. The advantages of the new biaxial tensile shear test method and some experimental findings are concluded.